Modelo de volatilidad y pronóstico del ingreso tributario del Gobierno Nacional. Perú, 2003 – 2021 - Chávez Paredes, Reny Jair (2023)
The purpose of this descriptive, observational, retrospective and longitudinal historical _x000D_ research was to establish the volatility model that best explains the tax payment of natural _x000D_ persons in Peru, using information from the Central Reserve Bank of Peru (BRCP). , from _x000D_ the period of January 2003-December 2021; applying the ARCH and GARCH models, _x000D_ due to the presence of heteroskedasticity, dividing the series into two periods: January _x000D_ 2003- December 2020 for model estimation, and January 2021-December 2021 for its _x000D_ validation, using the software as support media. statistical Eviews 10 and Microsoft _x000D_ Excel. Based on the results obtained, it was concluded that the ARCH (1) model was the _x000D_ best volatility model because it presented the lowest values in the Akaike, Schwarz and _x000D_ Hannan-Quinn information criteria. Finally, the forecasts made with this model about the _x000D_ monthly tax payment of natural persons in Peru for the year 2021, reported forecast error _x000D_ measures such as the mean absolute deviation, mean square error and mean error _x000D_ percentage, lower than those obtained. with other models.